STRUKTUR VEGETASI DAN CADANGAN KARBON TEGAKAN DI KAWASAN HUTAN CAGAR ALAM LEMBAH HARAU KABUPATEN LIMA PULUH KOTA SUMATERA BARAT - Muhammad Iko Pratama; Delvian Delvian; Kansih Sri Hartini (Program studi Kehutanan USU, 2016)
composition of plant species and the amount of carbon stocks stored in Nature Reserve Forest Lembah Harau at tree level and the level of the pole. The sampling intensity is 5 % of the total area of 270.5 ha. So that the total area of observation is 13.525 ha with a plot measuring 20 m x 100 m were 68 plots. In each plot were made sub-sub plot measuring 20 m x 20 m for tree and 10 m x 10 m for pole. Vegetation analysis use a combination of track method and swath line method, while the biomass estimation use non destructive sampling method. The results showed that 80 kinds of plants with a number of individuals as much as 246 individuals/ha. The highest important value indeks of tree species is Rhodelia teysmani with the value 53.33 %, while in the pole species is Nephelium mutabile with the value 46.30 %. The amount of carbon stocks stored in trees and poles are 62.57 ton/ha.Keywords : vegetation , carbon stock , nature reserve lembah harau